Molecular Age-Related Changes in the Anterior Segment of the Eye - Luis Fernando Hernandez-Zimbron; Rosario Gulias-Cañizo; María F. Golzarri; Blanca Elizabeth Martínez-Báez; Hugo Quiroz-Mercado; Roberto Gonzalez-Salinas (Journal of Ophthalmology)
Purpose. To examine the current knowledge about the age-related processes in the anterior segment of the eye at a biological, clinical, and molecular level. Methods. We reviewed the available published literature that addresses the aging process of the anterior segment of the eye and its associated molecular and physiological events. We performed a search on PubMed, CINAHL, and Embase using the MeSH terms “eye,” “anterior segment,” and “age.” We generated searches to account for synonyms of these keywords and MESH headings as follows: (1) “Eye” AND “ageing process” OR “anterior segment ageing” and (2) “Anterior segment” AND “ageing process” OR “anterior segment” AND “molecular changes” AND “age.” Results. Among the principal causes of age-dependent alterations in the anterior segment of the eye, we found the mutation of the TGF-β gene and loss of autophagy in addition to oxidative stress, which contributes to the pathogenesis of degenerative diseases. Conclusions. In this review, we summarize the current knowledge regarding some of the molecular mechanisms related to aging in the anterior segment of the eye. We also introduce and propose potential roles of autophagy, an important mechanism responsible for maintaining homeostasis and proteostasis under stress conditions in the anterior segment during aging.